Significant extra‐tropical anomalies in the lead up to the Black Saturday fires - Sonya L. Fiddes; Alexandre B. Pezza; James Renwick (International Journal of Climatology, 2016)
Black Saturday ( BS ), 7 February 2009, is recognized as Australia's most severe bushfire event on record. The meteorology that day, although extreme, was typical of southeast Australian bushfire events, characterized by gusty northerly winds before a cool change brought strong southerly winds and a dramatic temperature drop. This study investigates a range of extra‐tropical atmospheric (pressure, temperatures) and oceanic temperature anomalies that occurred on or leading up to BS . Results show several parameters were within the top 5% or were record breaking for the satellite era. Of particular note are the anomalies that occurred over the Antarctic region, having the strongest signal and appearing in unison with the pre‐ BS heatwave. We suggest that a combination of a warm polar ocean and an enhanced mid‐latitude thermal contrast in the Indian Ocean aided in triggering sub‐polar blocking and an intense cyclone, which brought the catastrophic cold front on BS .

Heat stress during the Black Saturday event in Melbourne, Australia - Stephanie J. Jacobs; Timo Vihma; Alexandre B. Pezza (International Journal of Biometeorology, 2015)

A new ‘bio-comfort’ perspective for Melbourne based on heat stress, air pollution and pollen - Stephanie J. Jacobs; Alexandre B. Pezza; Vaughan Barras; John Bye (International Journal of Biometeorology, 2014)